APLIKASI PUPUK CAIR DARI SAMPAH ORGANIK RUMAH TANGGA TERHADAP PRODUKSI TANAMAN SIRIH (Piper betle Linn.) - Wahida Wahida; Ni Luh Sri Suryaningsih (AGRICOLA, 2016)
Sirih plants is very important for Papuanese, because it is not only consumed, but also a very important ingredients in a traditional ceremonies. It is believed as brotherhood linkage, so it is very important to develop the production of sirih plants. This research aimed to utilize the organic household waste becoming liquid fertilizer which will be applicated on sirih plants with various dosage. The research was using Randomized Block Design, with six treatments of organic liquid fertilizer, which are: sirih plant with no treatments (D0), sirih plant with 10 ml/2L of water (D1), sirih plant with 20 ml/2L of water (D2), sirih plant with 30 ml/2L of water (D3), sirih plant with 40 ml/2L of water (D4) and sirih plant with 50 ml/2L of water (D5). Every treatment was repeated five times, so there were 30 experimental units. Observed parameters, are: number of branches, fruit length (cm), fruit diameter (mm), weight per fruit (g) and total fruit weight per plant (g). The treatments were applicated every two weeks. The data was analyzed with variance analysis. The observation showed that the treatments have no significant effects on fruit length, fruit diameter and weight per fruit, but have very significant effect on total fruit weight per plant. The best total fruit weight per plant is 88.70 g with 40 ml organic liquid fertilizer per 2L of  water.